2020
DOI: 10.1088/1748-0221/15/10/p10003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep gain layer and Carbon infusion on LGAD radiation hardness

Abstract: The properties of 50 μm thick Low Gain Avalanche Diode (LGAD) detectors manufactured by Hamamatsu photonics (HPK) and Fondazione Bruno Kessler (FBK) were tested before and after irradiation with neutrons. Their performance were measured in charge collection studies using β-particles from a 90Sr source and in capacitance-voltage scans (C-V) to determine the bias to deplete the gain layer. Carbon infusion to the gain layer of the sensors was tested by FBK in the UFSD3 production. HPK instead produced LGADs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…The outer radius of the FST is up to 45 cm to cover pseudorapidity from 1 to 3. Three silicon technologies, LGAD [533,534], MALTA [535][536][537] and the ALICE ITS-3 type sensor [538,539], are in consideration. The FST will implement two of these technologies to provide both good spatial and timing resolutions.…”
Section: Forward Tracking Studiesmentioning
confidence: 99%
“…The outer radius of the FST is up to 45 cm to cover pseudorapidity from 1 to 3. Three silicon technologies, LGAD [533,534], MALTA [535][536][537] and the ALICE ITS-3 type sensor [538,539], are in consideration. The FST will implement two of these technologies to provide both good spatial and timing resolutions.…”
Section: Forward Tracking Studiesmentioning
confidence: 99%
“…The radiation resilience of LGAD sensors, a relatively recent technology, is currently being investigated in view of applications in detectors at hadron colliders. Recent results have shown that the performances of LGAD sensors exposed to irradiation tests remain acceptable up to fluencies of around 10 15 n eq /cm 2 [80,81]. These fluencies, which are those expected for applications of LGAD sensors planned for the High Luminosity LHC detectors, correspond to total ionizing doses larger than Mrad [82], which are, in turn, larger than those expected for years of spacecraft operations in most of the orbits.…”
Section: Prospects Towards 5d Tracking In Space With Simsmentioning
confidence: 99%
“…The IHEP-IMEv2 and IHEP-IMEv1 LGAD sensors [12] were irradiated with neutrons at the JSI nuclear research reactor in Ljubljana [19,20]. Three different irradiation fluences were used: 0.8×10 15 , 1.5×10 15 , and 2.5×10 15 n eq /cm 2 .…”
Section: Neutron Irradiation and Beta Test Setupmentioning
confidence: 99%